Project-Based Learning Model with A Scientific Approach to Mathematics Learning in Covid-19 Pandemic - Arum Dwi Rahmawati; Djoko Hari Supriyanto; Wulan Ria Sari (STAI Hubbulwathan Duri, 2021)
This study aimed to determine the effect of using a project-based learning model with a scientific approach to students' mathematics learning. This kind of examination with experimental methods is included in quantitative research. This research design is a quasi-experiment. Samples were taken from 2 classes, the population in this exam was all class VIII SMP Negeri 3 Ngrambe in the 2020/2021 school year. The method used in sampling is cluster random sampling. Information retrieval procedures in this study using tests and documentation. The method of checking information uses instrument tests, prerequisite tests, and hypothesis testing. The results of information testing with a significant degree of 5% (0.05), namely the information data on the results of the lilliefors normality test. The learning outcomes of the experimental class L count L table (0.039 0.173), and the control class L count L table (0.031 0.173). It can be considered that the information data submitted is normal. Based on the information data on the homogeneity test results, pretest information data F max F table (1.24 1.98). It means that the information was homogeneous. Based on the information data on the results of hypothesis testing, pretest before treatment from the experimental class and the control class got t count t table (-0,501 1,677). The statement is likely acknowledged or, as a whole, there is no influence from the project-based model with a project-based learning model with a scientific approach to students' mathematics learning outcomes Posttest information data obtained by T count T table (3.566 2.063), in other words, the effect of the project-based learning model on students' mathematics learning outcomes in class VIII SMP Negeri 3 Ngrambe in the academic year 2020/2021.